Iraq and Turkey Study in political Relations 1980-1988 - Abo Lool Chibchab, Hameed (International Journal of Psychosocial Rehabilitation, 2020)
Iraq and Turkey are two countries linked by historical, cultural, and economic ties. The two countries have sought to develop their relationship since the Turkish recognition of Iraq in 1927, based on their common interests, especially since these two countries are linked by common borders and common issues, such as water, the Kurds, Turkmen, and finally oil. The existing relations between Iraq and Turkey are governed by a number of historical, economic, and cultural factors arising from the overlap of bilateral interests between the two countries. This study on Iraqi-Turkish political relations from 1980 to 1988 came with a hierarchical structure from the introduction and preamble and three topics dealing with preparation for the historical successor to Iraqi-Turkish relations. The first topic is the 1980 coup in Turkey led by Kenan Evren and the Iraqi government’s position on it; the second topic is Turkey’s position on the 1980 Iraq-Iran war to 1988; and the third topic is the Kurdish issue in Turkey and Iraq’s position on it. The conclusion came to contain a set of study results.